Effect of Jack Knife Stretching Versus Proprioceptive Neuromuscular Facilitation (Hold Relax) Stretching Technique in Asymptomatic Individuals with Hamstring Tightness: A Randomized Clinical Trial - Amruta Kabra1, Kajal Salekar2, Tanvi Kalanekar3, Kajal Salekar2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Study is to compare the effectiveness of Jack knife stretching and Proprioceptive Neuromuscular Facilitation (PNF) stretching Technique in asymptomatic individuals with hamstring tightness. Aims and Objectives : 1. To study the effect of jack-knife stretching on the individuals with asymptomatic hamstring tightness in terms of Active knee extension test, finger to floor, passive SLR and LEFS Questionnaire.2.To Study the effect of PNF stretching on individuals with asymptomatic hamstring tightness. 3.To compare the effect of Jack knife and PNF stretching in individuals with hamstring tightness. Material and Method: Ethical approval was obtained. 56 healthy subjects were assigned into two groups. PNF (hold relax) stretching technique was given to the Group A and Group B received Jack Knife stretching. Active knee extension test, Finger to floor test, Passive single leg raise test and Lower extremity functional scale these parameters were measured . Results: Intra-group comparison for all the outcome measures in both the groups showed statistical significance. Inter-group comparison for all the outcome measures for both the groups had differences but showed statistical significance. Group B Jack knife stretching was more effective than group A PNF (hold relax) stretching. Conclusion: The present study results indicate that to increase hamstring flexibility both the treatment techniques i.e PNF stretching and jack knife stretching are effective in asymptomatic individuals with hamstring tightness. Thus, our study shows jack knife stretching gives immediate effect due to closed pack position of stretching compared to open pack position of PNF group